Proceedings of the 2006 ACM SIGPLAN Workshop on Haskell 2006
DOI: 10.1145/1159842.1159850
|View full text |Cite
|
Sign up to set email alerts
|

Running the manual

Abstract: We propose a development methodology for designing and prototyping high assurance microkernels, and describe our application of it. The methodology is based on rapid prototyping and iterative refinement of the microkernel in a functional programming language. The prototype provides a precise semi-formal model, which is also combined with a machine simulator to form a reference implementation capable of executing real user-level software, to obtain accurate feedback on the suitability of the kernel API during d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We chose to build on Haskell's QuickCheck rather than Isabelle/HOL's QuickCheck because it is easier for Cogent programmers to use a testing framework that lies in the ecosystem of a functional programming language rather than interact with a theorem prover. Haskell acts as a good communication medium between programmers and proof engineers [14,26]. Moreover, due to Isabelle/HOL's interactive nature, testers would have to wait for Isabelle to re-process the proof scripts affected by a change in a theory file, before they can run tests again.…”
Section: Related Workmentioning
confidence: 99%
“…We chose to build on Haskell's QuickCheck rather than Isabelle/HOL's QuickCheck because it is easier for Cogent programmers to use a testing framework that lies in the ecosystem of a functional programming language rather than interact with a theorem prover. Haskell acts as a good communication medium between programmers and proof engineers [14,26]. Moreover, due to Isabelle/HOL's interactive nature, testers would have to wait for Isabelle to re-process the proof scripts affected by a change in a theory file, before they can run tests again.…”
Section: Related Workmentioning
confidence: 99%
“…seL4 Haskell has been used as a prototyping language for formally verified systems in the past. The seL4 verified microkernel started with a Haskell prototype that was semiautomatically translated to Isabelle/HOL [10]. As in our work, they were restricted to the terminating fragment of Haskell.…”
Section: Translating Haskell To Higher-order Logicmentioning
confidence: 99%
“…Haskell has been used as a prototyping language for mechanically verified systems in the past. The seL4 verified microkernel started with a Haskell prototype that was semi-automatically translated to Isabelle/HOL [Derrin et al 2006;Klein et al 2009]. The authors found that the availability of the Haskell prototype provided a machine-checkable formal executable specification of the system.…”
Section: Verification Tools For Haskellmentioning
confidence: 99%